2002
DOI: 10.1128/iai.70.4.2245-2248.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role ofNeisseria meningitidis luxSin Cell-to-Cell Signaling and Bacteremic Infection

Abstract: Numerous pathogenic bacteria contain luxS, which is required for autoinducer-2 production. Here, we demonstrate that Neisseria meningitidis contains a functional copy of luxS that is necessary for full meningococcal virulence; strains with a luxS deletion are defective for bacteremia, a prerequisite of meningococcal pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…Using this model, we showed that the S. marcescens 274 luxS mutant exhibits a subtle but reproducible virulence defect. Attenuation of virulence has been seen in various luxS mutants, for example in N. meningitidis, V. vulnificus and Streptococcus pneumoniae; although in other bacteria, virulence is not significantly altered in the luxS mutant, at least in the chosen model (Burgess et al, 2002;Kim et al, 2003;Schneider et al, 2002;Stroeher et al, 2003;Winzer et al, 2002b). The reduced production of haemolysin and/or prodigiosin by the luxS mutant of S. marcescens 274 may contribute to its altered virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this model, we showed that the S. marcescens 274 luxS mutant exhibits a subtle but reproducible virulence defect. Attenuation of virulence has been seen in various luxS mutants, for example in N. meningitidis, V. vulnificus and Streptococcus pneumoniae; although in other bacteria, virulence is not significantly altered in the luxS mutant, at least in the chosen model (Burgess et al, 2002;Kim et al, 2003;Schneider et al, 2002;Stroeher et al, 2003;Winzer et al, 2002b). The reduced production of haemolysin and/or prodigiosin by the luxS mutant of S. marcescens 274 may contribute to its altered virulence.…”
Section: Discussionmentioning
confidence: 99%
“…in Helicobacter pylori and Proteus mirabilis), through to altered production of virulence determinants (e.g. in Porphyromonas gingivalis, Streptococcus pyogenes and Clostridium perfringens), and decreased virulence (in Neisseria meningitidis, Streptococcus pneumoniae and Vibrio vulnificus) (Burgess et al, 2002;Joyce et al, 2000;Kim et al, 2003;Lyon et al, 2001;Ohtani et al, 2002;Schneider et al, 2002;Stroeher et al, 2003;Winzer et al, 2002b). However, the elucidation of the biosynthetic pathway of AI-2 has revealed a metabolic role for LuxS, in the S-adenosylmethionineutilization pathway (Schauder et al, 2001;Winzer et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…typhimurium, Sh. flexneri and Strep. pyogenes (Sperandio et al, 1999 ;Forsyth & Cover, 2000 ;Joyce et al, 2000 ;Burgess et al, 2002 ;Day & Maurelli, 2001 ;Lyon et al, 2001 ;Winzer et al, 2002). Although a DNA-microarray-based approach suggested that several hundred genes were up-or down-regulated in an E. coli O157 : H7 luxS mutant (Spernandio et al, 2001), these changes have not yet been linked to a lack of AI-2 activity, and may in fact be explained by additional functions of the luxS gene product.…”
Section: Introductionmentioning
confidence: 99%
“…In Vibrio harveyi, the LuxS protein is required for the production of a signal molecule of unknown structure, autoinducer 2 (AI-2), which exerts its activity via a complex phospho-relay system. AI-2 activity has been discovered in spent culture supernatants of many organisms, including Escherichia coli, Helicobacter pylori, Neisseria meningitidis, Porphyromonas gingivalis, Streptococcus pyogenes, Shigella flexneri and Salmonella typhimurium (Bassler et al, 1997 ;Surette & Bassler, 1998 ;Sperandio et al, 1999 ;Forsyth & Cover, 2000 ;Joyce et al, 2000 ;Burgess et al, 2002 ;Day & Maurelli, 2001 ;Lyon et al, 2001 ;Winzer et al, 2002). Furthermore, highly conserved LuxS homologues have been identified in a large number of pathogenic and nonpathogenic bacteria by database analysis Bassler, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with its proposed role as an interspecies communication signal, AI-2-mediated signal transduction circuits have been found to regulate biological processes that coordinate the behaviour of cells as a community to best adapt to various environmental situations. Such biological processes include biofilm formation, conjugation, sporulation, and production of virulence elements (Gonzalez Barrios et al, 2006;McNab et al, 2003;Rickard et al, 2006;; the last has been linked to the LuxS/AI-2 quorumsensing system via, most often, mutational studies of the luxS gene (Lyon et al, 2001;Marouni & Sela, 2003;Ohtani et al, 2002;Stroeher et al, 2003;Winzer et al, 2002b;Zhu et al, 2002). been reported to occur in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%